STUDY OF EXHAUST GAS RESIDUAL HEAT CONVERSION HRSG PLTGU KERAMASAN TO ELECTRICAL ENERGY WITH GENERATOR THERMOELECTRIC TECHNOLOGY - Firmansah, Hari; Bizzy, Irwin; Mataram, Agung; Sipahutar, Riman (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The Heat Recovery Steam Generator (HRSG) is a combination of a Gas Power Plant (PLTG) and a Steam Power Plant (PLTU), this plant utilizes exhaust gas from the PLTG to produce steam as the working fluid in the PLTU. The residual heat from the heating process at the HRSG is channeled into the chimney, and the remaining heat from the exhaust gas can be converted into electrical energy with the Thermoelectric Generator (TEG) module. This research was carried out by installing the TEG module in series on the surface of the HRSG chimney wall, using laboratory scale measurements. The heat source uses a heater with a total power of 2,000 W. The research results show that the TEG module can convert the residual heat energy of the exhaust gas from the HRSG chimney into electrical energy. Four TEG modules mounted on the chimney surface can generate a voltage of 0.83 V and a maximum power of 2.79 mW. These results indicate that the TEG module is an opportunity to convert heat energy into electrical energy for further development.